Fetus Papyraceus: a rare case report - Masamatti, Smita Surendra; Ramteerthakar, Nayan Anant; Pandav, Amit Bapuso; Gosavi, Alka Vikas (Annals of Pathology and Laboratory Medicine, 2014)
Fetus papyraceus (FP) also called fetus compressus is a mummified and compressed fetus as a result of fetal death during multiple pregnancy.Â Fetus papyraceus is a rare condition and is associated with obstetric complications. Sonography is a visual tool to confirm the diagnosis, but it is not always possible due to anatomical position and technical difficulties. FP is usually discovered among the placenta and membranes of its well developed twin. Searching for a fetus papyraceus should be a routine part of placental examination.Â Â